2016
DOI: 10.1038/nsmb.3279
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a pathogen effector reveals the enzymatic mechanism of a novel acetyltransferase family

Abstract: Effectors secreted by the type III secretion system are essential for bacterial pathogenesis. Members of the Yersinia outer-protein J (YopJ) family of effectors found in diverse plant and animal pathogens depend on a protease-like catalytic triad to acetylate host proteins and produce virulence. However, the structural basis for this noncanonical acetyltransferase activity remains unknown. Here, we report the crystal structures of the YopJ effector HopZ1a, produced by the phytopathogen Pseudomonas syringae, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 45 publications
1
62
0
Order By: Relevance
“…Since the antibody (α-AcK) we used for testing HopZ5 autoacetylation did not allow us to detect non-lysine acetylation, additional autoacetylation of other residues in HopZ5 may still occur in both C218A and K278R variants. The crystal structure of HopZ1a revealed that the analogous residue to K278 in HopZ5, K211 in HopZ1a, is involved in coordination of the plant-derived cofactor IP6 20 . This suggests that HopZ5 K278 could also be involved in coordination of IP6 and thus loss of this residue in the K278R variant results in loss of acetylation activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the antibody (α-AcK) we used for testing HopZ5 autoacetylation did not allow us to detect non-lysine acetylation, additional autoacetylation of other residues in HopZ5 may still occur in both C218A and K278R variants. The crystal structure of HopZ1a revealed that the analogous residue to K278 in HopZ5, K211 in HopZ1a, is involved in coordination of the plant-derived cofactor IP6 20 . This suggests that HopZ5 K278 could also be involved in coordination of IP6 and thus loss of this residue in the K278R variant results in loss of acetylation activity.…”
Section: Discussionmentioning
confidence: 99%
“…syringae pv. syringae A2 autoacetylates a specific threonine residue (T346) with the involvement of two serine residues (S349 and S351) following in planta activation of HopZ1a by the plant cofactor IP6 20, 21 . In addition, HopZ1a acetylates jasmonate ZIM-domain (JAZ) repressors of jasmonic acid (JA) signalling leading to their proteosomal degradation, thereby activating the JA pathway and antagonizing salicylic acid-mediated disease resistance 22 .…”
Section: Introductionmentioning
confidence: 99%
“…cofactors). Examples include the activation of the AvrRpt2 protease by the eukaryotic cyclophilin, ROC1 (Coaker et al, 2005(Coaker et al, , 2006 and the activation of the HopZ1a acetyltransferase by phytic acid (Lee et al, 2012;Zhang et al, 2016). A third category includes 'sensor' targets that typically associate with NLR proteins, and promote ETI (Khan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, effector biology has facilitated the discovery of biological processes. Examples of recently discerned effector biochemistries include: a newly identified mechanism of PTM (Zhang, Ma, et al 2016), novel PTMs (e.g. uridylation of several receptor like-cytoplasmic kinases by AvrAC, (Feng et al 2012); acetylation of histidines, (Lee et al 2015) and novel metabolites (Schuebel et al 2016).…”
Section: Foundational Research Needs Opportunities and Challengesmentioning
confidence: 99%